Fitness testing as a discriminative tool for the diagnosis and monitoring of fibromyalgia. Issue 4 (24th October 2011) - Aparicio, V. A.; Carbonell‐Baeza, A.; Ruiz, J. R.; Aranda, P.; Tercedor, P.; Delgado‐Fernández, M.; Ortega, F. B.
Abstract : We aimed to determine the ability of a set of physical fitness tests to discriminate between presence/absence of fibromyalgia (FM) and moderate/severe FM. The sample comprised 94 female FM patients (52 ± 8 years) and 66 healthy women (54 ± 6 years). We assessed physical fitness by means of the 30‐s chair stand, handgrip strength, chair sit and reach, back scratch, blind flamingo, 8‐feet up and go, and 6‐min walking tests. Patients were classified as having moderate FM if the score in the Fibromyalgia Impact Questionnaire (FIQ) was <70 and as having severe FM if the FIQ was ≥70. FM patients and patients with severe FM performed worse in most of the fitness tests studied ( P  < 0.001). Except the back scratch test, all the tests were able to discriminate between presence and absence of FM [area under the curve (AUC) = 0.66 to 0.92; P  ≤ 0.001], and four tests also discriminated FM severity (AUC = 0.62 to 0.66; P  ≤ 0.05). The 30‐s chair stand test showed the highest ability to discriminate FM presence and severity (AUC = 0.92, P  < 0.001; and AUC = 0.66, P  = 0.008, respectively), being the corresponding discriminating cutoffs 9 and 6 repetitions, respectively. Physical fitness in general, and particularly the 30‐s chair stand test, is able to discriminate between women with FM from those without FM, as well as between those with moderate FM from their peers with severe FM.